Gregory of Nyssa's Work in St. Euthymius the Athonite's Translation: Euthymius the Athonite's Translation (Gregory of Nyssa, On Virginity. Edited by Protopresbyter Giorgi Zviadadze, "Meridiani", Tbilisi, 2011 - Elguja Khintibidze, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
In 2011 protopresbyter Giorgi Zviadadze published S.t Gregory of Nyssa's ascetic treatise On Virginity. The edition answers the latest standards of modern philological scholarship. The researcher editor has brought to light highly significant details of the translation method of the Georgian translator St. Euthymius the Athonite.